Delivery of a hydrophobic phthalocyanine photosensitizer using PEGylated gold nanoparticle conjugates for the in vivo photodynamic therapy of amelanotic melanoma12. Issue 5 (11th April 2016) - Camerin, Monica; Moreno, Miguel; Marín, María J.; Schofield, Claire L.; Chambrier, Isabelle; Cook, Michael J.; Coppellotti, Olimpia; Jori, Giulio; Russell, David A.
Abstract : Gold nanoparticles functionalised with PEG and a phthalocyanine photosensitiser achieved 40% no tumour regrowth and complete survival following in vivo PDT. Abstract : Photodynamic therapy (PDT) is a treatment of cancer whereby tumours are destroyed by reactive oxygen species generated upon photoactivation of a photosensitizer drug. Hydrophobic photosensitizers are known to be ideal for PDT; however, their hydrophobicity necessitates that they are typically administered using emulsions. Here, a delivery vehicle for photodynamic therapy based on the co-self-assembly of both a Zn(ii )-phthalocyanine derivative photosensitizer and a polyethylene glycol (PEG) derivative onto gold nanoparticles is reported. The PEG on the particle surface ensured that the conjugates were water soluble and enhanced their retention in the serum, improving the efficiency of PDT in vivo . The pharmacokinetic behaviour of the nanoparticle conjugates following intravenous injection into C57/BL6 mice bearing a subcutaneous transplanted B78H1 amelanotic melanoma showed a significant increase of retention of the nanoparticles in the tumour. PDT tumour destruction was achieved 3 h following injection of the nanoparticle conjugates leading to a remarkable 40% of the treated mice showing no tumour regrowth and complete survival. These results highlight that dual functionalised nanoparticles exhibit significant potential in PDT of cancer especially for difficult to treat cancers such as amelanotic melanoma.